Antimicrobial Resistance Challenged with Platinum(II) and Palladium(II) Complexes Containing 1,10-Phenanthroline and 5-Amino-1,3,4-Thiadiazole-2(3H)-Thione in Campylobacter jejuni - Meiry Leandra de Lacerda; Daise Aparecida Rossi; Eduarda Cristina Alves Lourenzatto; Micaela Guidotti Takeuchi; Wesley Almeida Souza; Raphael Tristão Cruvinel Silva; Luma Gonçalves Julio; Wendell Guerra; Roberta Torres de Melo (MDPI AG, 2022)
This work describes the synthesis and characterization of two metal complexes of the type [M(L1)2(phen)], where M = Pt2+ (complex I) or Pd2+ (complex II), L1 = 5-amino-1,3,4-thiadiazole-2(3H)-thiolate and phen = 1,10-phenanthroline. The in vitro antibacterial activity of these complexes was investigated in isolation and synergistically with ciprofloxacin (CIP) and erythromycin (ERY) in three strains of Campylobacter jejuni (MIC = 32 mg/L for CIP and ERY), selected from a bank of 235 strains representative of three poultry exporting states of the country (A, B and C), previously analyzed for epidemiology and resistance to CIP and ERY. A total of 53/235 (22.55%) strains showed co-resistance to CIP and ERY. Isolated resistance to CIP was higher than to ERY. Epidemiological analysis showed that resistance to CIP was more evident in state B (p < 0.0001), as well as a higher susceptibility to ERY in state C (p = 0.0028). Co-resistance was expressive in state A and in the spring and fall seasons. The evaluation of I alone and in synergy with CIP and ERY found values up to 0.25 mg/L not significant for ERY. Complex II did not show an antimicrobial effect on the three strains of tested C. jejuni. The effect provided by complex I represents a promising alternative for control of resistant strains of C. jejuni.